2012
DOI: 10.1159/000345329
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Genetic and Environmental Factors Associated with Congenital Vertebral Malformations

Abstract: Congenital vertebral malformations (CVM) pose a significant health problem because they can be associated with spinal deformities, such as congenital scoliosis and kyphosis, in addition to various syndromes and other congenital malformations. Additional information remains to be learned regarding the natural history of congenital scoliosis and related health problems. Although significant progress has been made in understanding the process of somite formation, which gives rise to vertebral bodies, there is a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 127 publications
0
80
0
7
Order By: Relevance
“…Skeletal malformations, particularly vertebral malformations, were the most common malformations observed in our cohort. Vertebral malformations have a prevalence of 0.5 to 1 per 1000 live births and may involve 1 or multiple vertebra . Vertebral malformations are common birth defects among newborns with 16p11.2 recurrent microdeletion.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal malformations, particularly vertebral malformations, were the most common malformations observed in our cohort. Vertebral malformations have a prevalence of 0.5 to 1 per 1000 live births and may involve 1 or multiple vertebra . Vertebral malformations are common birth defects among newborns with 16p11.2 recurrent microdeletion.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with other blastogenetic and non-blastogenetic malformations, costovertebral anomalies can be observed in dozens of syndromes, as recently reviewed for multiple vertebral segmentation defects [Giampietro et al, 2013]. Their origin is obscure in otherwise healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it could also be due to an issue in data analysis, thus raising the hypothesis of a non-Mendelian model with multigenic and epigenetic factors. Indeed, environmental factors like hypoxia during gestation have been shown to increase the SDV rate when associated with fetal haploinsufficiency of HES7 , MESP2 , DLL1 or NOTCH1 ,21 or with maternal conditions in mice 11…”
Section: Discussionmentioning
confidence: 99%
“…Well-described syndromes are found in each category, notably with Klippel-Feil syndrome, which is associated with variants in GDF3 , GDF6 , MYO18B and MEOX1 8; spondylocarpotarsal synostosis syndrome, associated with variants in FLNB 9; and Currarino syndrome, associated with variants in MNX1 10. M-SDV can also be secondary to neuromuscular disorders and teratogenic exposure (alcohol, valproic acid, phenytoin…) 11. It has been shown that some environmental factors, like short-term gestational hypoxia, increase the penetrance and severity of SDV 12…”
Section: Introductionmentioning
confidence: 99%